1999
DOI: 10.1142/s0218301399000069
|View full text |Cite
|
Sign up to set email alerts
|

Photon Emission by an Ultra-Relativistic Particle Channeling in a Periodically Bent Crystal

Abstract: This paper is devoted to a detailed analysis of the new type of undulator radiation generated by an ultra-relativistic charged particle channeling along a crystal plane, which is periodically bent by a transverse acoustic wave, as well as to the conditions limiting the observation of this phenomenon. This mechanism makes feasible the generation of electromagnetic radiation, both spontaneous and stimulated, emitted in a wide range of the photon energies, from X-up to 7-rays. II Int. J. Mod. Phys. E 1999.08:49-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
292
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(305 citation statements)
references
References 42 publications
13
292
0
Order By: Relevance
“…This quantity can be estimated as L d (0) = (256/9π 2 )(a TF dγ/r 0 Λ c ) [3,19], where r 0 and a TF are the classical radius of the electron and the Thomas-Fermi radius of the crystal atom, and Λ c = ln( √ 2γ mc 2 /I) − 23/24 (I stands for an average ionization potential of the atom). The factor (1 − C) 2 takes into account the decrease of the interplanar potential well due to periodic bendings.…”
Section: Dechanneling Length Of Positrons and Electrons In A Periodicmentioning
confidence: 99%
See 3 more Smart Citations
“…This quantity can be estimated as L d (0) = (256/9π 2 )(a TF dγ/r 0 Λ c ) [3,19], where r 0 and a TF are the classical radius of the electron and the Thomas-Fermi radius of the crystal atom, and Λ c = ln( √ 2γ mc 2 /I) − 23/24 (I stands for an average ionization potential of the atom). The factor (1 − C) 2 takes into account the decrease of the interplanar potential well due to periodic bendings.…”
Section: Dechanneling Length Of Positrons and Electrons In A Periodicmentioning
confidence: 99%
“…This quantity is tabulated for a number of elements and over wide ranges of photon frequencies [17]. It is worth noting that for sufficiently high photon energies ( ω ≥ 10 2 keV) the restriction on the length of undulator due to the photon attenuation effect becomes much less severe than to the dechanneling process [2,3,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystalline undulators (CU) with periodically deformed crystallographic planes offer huge electromagnetic fields and could provide a quite short period L of an undulator in sub-millimeter range. This way one can also arrange for substantial amplitudes A of oscillation for the particles channeled through the undulator and thus increase the intensity of the radiation.Currently, bent crystals are largely used for channeling extraction of 70-GeV protons at IHEP (Protvino) with efficiency reaching 85% at intensity well over 10 12 particle With a strong world-wide attention to novel sources of radiation, there has been broad theoretical interest to compact crystalline undulators, with some approaches covering also nanotechnology to make use of nanotubes to guide radiating particles [4][5][6][7][8][9][10][11][12] In bent crystal channeling experiments at IHEP Protvino with 70-GeV protons, it was found that accidental micro-scratches on a crystal surface caused a deformation of the crystallographic planes to substantial depths, down to a few hundred microns as depicted in Fig. 1(a).…”
mentioning
confidence: 99%